ملامح الاستدامة البيئية في العمران قديما وحديثا - بوبيـش, فريـد (University of Eloued جامعة الوادي, 2015)
أصبحت قضية البيئة في وقتنا الراهن مطلبا مهما من الضروري التفاعل معه والاستجابة لمتطلباته، وعلى مستوى جميع القطاعات بما فيه القطاع العمراني. خاصة وأن حكومات العالم قد بدأت تؤكد على ضرورة دعم البحوث والصناعات التي تجعل من مباني المستقبل أكثر كفاءة في استخدام الطاقة، وأكثر ترشيدا لمواردنا البيئية، وبالتالي أكثر استدامة من الناحية البيئية. وبناء عليه جاءت هذه الدراسة لتجيب عن السؤالين الآتيين: إلى أي مدى كانت المجتمعات الإنسانية تُعنى بقضية الاستدامة البيئية في مجال العمران؟ وهل يمكن استقراء ملامح للاستدامة البيئية في العمران قديما وحديثا؟ الكلمات المفتاحية: الاستدامة البيئية، العمران، العمران المستديم. The features of environmental sustainability in urbanism, past and present Abstract : Environmental issue nowadays has become very important, so it became necessary to respond to its requirements, and at the level of all sectors, including the urban sector. Especially since the governments of the world have begun to emphasize the need to support research and industries which make future buildings more energy efficient, and more rational environmental resources, and thus more environmentally sustainable. Accordingly, this study was to answer the following two questions: To what extent was the humane societies concerned with the issue of environmental sustainability in the field of urbanism? Is it possible to extrapolate the features of environmental sustainability in urbanism, past and present? Keywords: Environmental sustainability, urbanism, sustainable urbanism.
مقال بمجلة الدراسات والبحوث الاجتماعية
Keywords: الاستدامة البيئية، العمران، العمران المستديم